Developing Problem Based Biodiversity Modules to Enhance 4C Skills and Scientific Literacy in Islamic Vocational High School - Fitriyani, Dina; Hasairin, Ashar; Silitonga, Melva (Jurnal Perspektif, 2025)
The purpose of this study was to determine the validity, practicality, and effectiveness of the biology learning module on Critical Thinkings, Creativity, Communication, and Collaboration (4C) skills, and students' biological literacy skills. This type of research is development research using the Analyze, Design, Develop, Implement, and Evaluate (ADDIE) model development. The subjects of this study were 30 students of class X of SMA Al Ulum Medan. The results of this study are the validity of the problem-based learning module in improving 4C skills and students' biological literacy skills are included in the valid category, so that the developed learning module has met the validity indicators. The practicality of the problem-based learning module in 4C skills and students' biological literacy skills is included in the practical category. The effectiveness of the 4C skills learning module and students' biological literacy skills based on the problem-based model meets the effectiveness criteria.